A Content Analysis of Writing Tasks in English Textbook “Think Globally Act Locally” of Junior High School - Widya Noviana Noor; Fariska Amelia Chaerani (WIDYABORNEO, 2022)
The purpose of the study is to explore and describe how well the type of writing task offered in the textbook matches up to the type of writing task proposed by Paul Nation. The study used qualitative research with a content analysis technique. Based on Louis Cohen the study process of data analysis technique through content analysis are follow: Selecting, classification, analyzing, and Inference. To calculate the results of data results, the researcher calculates percentages using Arikunto’s quality categorization schema. The data obtained from the English textbook “Think Globally Act Locally” for Junior High School’s Ninth Grade Depending on the theory that researcher used on English textbook, analysis found three kinds of writing tasks: experience tasks, guided tasks, and independent tasks. However, neither of the writing tasks were completed.supplied by this textbook suit the sorts of shared tasks. The dominant of writing task way found on this English textbook was guided task (51.7%).